An investigation of life quality of patients after two different acoustic neuroma resections. (3rd July 2019) - Ning, Fei; Zuo, Haiwei; Guo, Lei; Jiao, Changling; Xu, Xiaoping; Kong, Bingbing; Yang, Shiming
Abstract: Background: Patients may suffer postoperative facial nerve injury, hearing loss, or other postoperative complications after the operation, which seriously affect their postoperative life quality. Aims/objectives: To investigate the differences in QOL (quality of life) of patients with acoustic neuroma resection by the translabyrinthine or retrosigmoid approach. Material and methods: Patients with acoustic neuroma resection in our department were enrolled in this experimental study, among which fifty patients underwent the translabyrinthine approach resection, the other 50 patients underwent the retrosigmoid approach resection. Different scores by the SF-36 scale between these two groups of patients one month after discharge were then analyzed. Results: Scores of patients undergoing the retrosigmoid approach were higher in the three dimensions of Social Functioning, Role-emotional and Mental Health than those of patients undergoing the translabyrinthine approach with statistical significance. However, scores of patients undergoing the translabyrinthine approach were higher in the two dimensions of Body Pain and Vitality than those of the patients undergoing the retrosigmoid approach. Conclusions and significance: The results indicated that individual nursing interventions for different patients are necessary to improve the QOL of patients after hospitalization. Moreover, the operated patients with translabyrinthine approach were more advantage than patients with retrosigmoid approach.